Sensors data collection framework using mobile identification with secure data sharing model - Fulayjan Alanazi; Ahmed Elhadad; Safwat Hamad; A Ghareeb (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Sensors are the modules or electronic devices that are used to measure and get environmental events and send the captured data to other devices, usually computer processors allocated on the cloud. One of the most recent challenges is to protect and save the privacy issues of those sensors data on the cloud sharing. In this paper, sensors data collection framework is proposed using mobile identification and proxy re-encryption model for data sharing. The proposed framework includes: identity broker server, sensors managing and monitoring applications, messages queuing sever and data repository server. Finally, the experimental results show that the proposed proxy re-encryption model can work in real time.